Recombinant Adeno-associated Virus 9-mediated Expression of Kallistatin Suppresses Lung Tumor Growth in Mice - Qu, Weihong; Zhao, Jianguo; Wu, Yaqing; Xu, Ruian; Liu, Shaowu (Current Gene Therapy, 2021)
Background: Lung cancer remains the most common cause of cancer-related deaths in China and worldwide. Traditional surgery and chemotherapy do not offer an effective cure, although gene therapy may be a promising future alternative. Kallistatin (Kal) is an endogenous inhibitor of angiogenesis and tumorigenesis. Recombinant adeno-associated virus (rAAV) is considered the most promising vector for gene therapy of many diseases due to persistent and long-term transgenic expression. Objective: The aim of this study was to investigate whether rAAV9-Kal inhibited NCI-H446 subcutaneous xenograft tumor growth in mice. Methods: The subcutaneous xenograft mode was induced by subcutaneous injection of 207 H446 cells into the dorsal skin of BALB/c nude mice. The mice were administered with ssrAAV9-Kal (single- stranded rAAV9) or dsrAAV9-Kal (double-stranded rAAV9) by intraperitoneal injection (I.P.). Tumor microvessel density (MVD) was examined by anti-CD34 staining to evaluate tumor angiogenesis. Results: Compared with the PBS (blank control) group, tumor growth in the high-dose ssrAAV9-Kal group was inhibited by 40% by day 49, and the MVD of tumor tissues was significantly decreased. Conclusion: The results indicate that this therapeutic strategy is a promising approach for clinical cancer therapy and implicate rAAV9-Kal as a candidate for gene therapy of lung cancer.
Keywords: subcutaneous xenograft tumor growth